Synthesis of a Co–Mo sulfide catalyst with a hollow structure for highly efficient hydrodesulfurization of dibenzothiophene. Issue 23 (23rd October 2017) - Li, Guangci; Yue, Li; Fan, Ruikun; Liu, Di; Li, Xuebing
Abstract : Co–Mo sulfides with tube-like structures exhibit super high activity for HDS of DBT. Abstract : A facile template-free method is developed to prepare porous Co–Mo sulfide sub-microtubes with open-ended structures via sulfurization of the Co–Mo precursor in an ethanol solution of CS2 . The hollow structure significantly improves the exposure degree of active components, resulting in an ultra-high activity for HDS of dibenzothiophene.